Letter from the Department of Airports and Harbors - Thomas M. Volk::::::
A letter from the Department of Airports and Harbors director Thomas M. Volk discussing an action taken by the Ventura County Board of Supervisors in regards to the desire to obtain the former Oxnard Air Force Base.